2001
DOI: 10.1096/fj.00-0547fje
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic, tri-block copolymers provide potent membrane-targeted neuroprotection

Abstract: Excitatory amino acid receptor activation and reactive oxygen species production are important mediators of neuronal death following acute brain injury and can lead to loss of membrane integrity. Poloxamer 188 (P188) is an amphiphilic, polyethylene-polypropylene-polyethylene copolymer that restores plasma membrane integrity of nonneuronal cells following membrane injury. Here, we demonstrate that P188 provides profound protection of hippocampal and cerebellar neurons following severe excitotoxic and oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 45 publications
3
84
0
Order By: Relevance
“…Pluronic block copolymers F68 and related F127 have been reported to have broad utilities and biological properties: Copolymers with higher hydrophilic/lipophilic balance (HLB) (e.g. F-68, HLB0.80) were shown to be capable of being inserted into lipid bilayer membranes and able to restore the integrity of damaged membranes [1013]; F68 was also shown to be capable of inhibiting protein aggregation [14]. These biological properties seem to be in large contrast to those from PEG, and offer the potential to increase the selectivity of EV precipitation when enriching from complex biofluids, such as plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Pluronic block copolymers F68 and related F127 have been reported to have broad utilities and biological properties: Copolymers with higher hydrophilic/lipophilic balance (HLB) (e.g. F-68, HLB0.80) were shown to be capable of being inserted into lipid bilayer membranes and able to restore the integrity of damaged membranes [1013]; F68 was also shown to be capable of inhibiting protein aggregation [14]. These biological properties seem to be in large contrast to those from PEG, and offer the potential to increase the selectivity of EV precipitation when enriching from complex biofluids, such as plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Exposing electroporated cells to this surfactant effectively seals the damaged membranes; thereby, acutely arresting the leakage of intracellular components in vivo and in vitro (Hanning et al, 2000;Lee et al, 1992Lee et al, , 1994Merchant et al, 1998;Terry et al, 1999;Borgens et al, 2004). Recently, Marks et al (2001) reported that P188 is effective in restoring the integrity of injured membranes of electroporated neuronal cells. Since the mechanisms of P188 action are specifically directed at the plasma membrane, the use of this surfactant may provide an alternative approach to treat both acute and delayed post-traumatic injuries in neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…26,31 Preliminary results showed that these polymers might be involved in the repair of proteins as well. 24 Towards our long term goal to learn about the effects of Poloxamers in the recovery of the cells and tissues, we plan to gain a fundamental understanding of the interaction of these polymers with different proteins in their denatured states.…”
Section: Introductionmentioning
confidence: 99%